Empowering Role Of Family Welfare (Pkk) In Improving The Quality Of Life In The Rinding Allo Village, North Luwu - Muh. Shadri Kahar Muang (IAIN Palopo, 2021)
This study discusses the role of Family Welfare Empowerment (PKK) in Improving Quality of Life Society this study. 1) How PKK build motivation and cooperation in a program, 2) How PKK role in building the quality of life in Rinding Allo Village. The purpose of this research is to build unity or cooperation PKK in memberian motivation to villagers and to improve the quality of life in business opportunities. The benefits of this research is the academic benefits, to broaden the village PKK in improving women, also can be used as material for further research relating to the role of the PKK problem, especially in human resource development. Benefits Practice, as a material to further understanding of the role of the PKK in improving the quality of the village and provide additional knowledge to the PKK in the implementation of programs and the Role of the Family Welfare Empowerment (PKK) in Improving Quality of Life Community in Rinding Allo Village, North Luwu. The method used in this study is a qualitative method using primary and secondary data sources. Primary data is an object or original documents or also the raw material of the perpetrators. Data collected from the actual situation when the event occurred, and secondary data is data obtained indirectly. In this case the data obtained from books, personal documents, family data from the village, journals or other articles related to this research.